Integrating Plastic Waste Pyrolysis Technology into STEM Education to Improve Students' Environmental Knowledge and Attitude - Nursaadah, Euis; Fannyda, Raidatul; Shabrina, Annida Nurul; Ruyani, Aceng (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2025)
The growing concern over plastic waste pollution and its harmful byproducts, such as CO, CO₂, NOₓ, and SOₓ gases from incineration, necessitates alternative and environmentally responsible waste management strategies. At MAN Insan Cendekia Bengkulu Tengah, a boarding school that manages its own waste, the integration of pyrolysis as a cleaner method for plastic waste treatment offers both practical and educational value. This study aimed to contextualize plastic waste pyrolysis within STEM-based learning to enhance students’ environmental knowledge and attitudes through interdisciplinary instruction. A quasi-experimental two-group pre-test–post-test design was employed, involving 32 students divided equally into control and experimental groups. The control group received STEM instruction using a module and video on plastic pyrolysis, while the experimental group engaged in a more immersive approach involving the same materials supplemented with hands-on pyrolysis activities. Results indicated that the experimental group outperformed the control group, with an environmental knowledge normalized gain (N-gain) score of 0.67 (medium), compared to 0.47 (low) in the control group. Additionally, the experimental group achieved higher environmental attitude scores (85) than the control group (76). These findings demonstrate that STEM education incorporating contextual, multimodal, and practical components can significantly enhance students’ conceptual understanding and engagement with environmental issues. The study contributes to the growing body of evidence supporting experiential STEM education as an effective approach for fostering environmental awareness and action in secondary education settings.